Genotoxicity and DNA repair indicative in blood cells after occupational exposure to ionizing radiation - Silva, Ronald Gerard (2016)
Occupational exposure to ionizing radiation (IR) can damage DNA. The study evaluated the genotoxic profile and repair indicatives of DNA from peripheral blood lymphocytes of health workers exposed occupationally to IR by adopting comet assay. Biomonitoring was done with ninety individuals; among them 45 were health professionals and the rests were non-professionals. Blood samples were collected after 48 h (2 d; non-exposed) and 168 h (7 d; exposed). The 7 d IR exposed group significantly increased in the rates and frequency of damage, while 2 d unexposed group exhibited more than 20% of DNA repair as compared to the respective control groups. The DNA damage was observed in more significant to the younger workers (18-27 y). However, the hematological abnormalities were not observed, despite of their positive correlation in genotoxic profile. Significant and positive correlations were observed in relation to the used medicaments, low consumption of vegetables as well as the type and place of work. In conclusion, biomarkers involved in comet assay can be applied in biomonitoring of genetic instability, including IR induced phenomena.